2021
DOI: 10.1111/jocn.16142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telehealth interventions on performing activities of daily living and maintaining balance in stroke survivors: A systematic review and meta‐analysis of randomised controlled studies

Abstract: Background: Stroke is one of the most common causes of disability worldwide. In recent years, diverse telehealth programmes for stroke survivors have suggested that this mode of rehabilitation could improve stroke survivors' abilities to perform activities of daily living (ADLs) and maintain balance. Although increasingly utilised in clinical and community settings, the effectiveness of telehealth interventions in stroke survivors remains inconclusive. This warrants investigation so that telehealth interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
1
8
0
1
Order By: Relevance
“…In comparison with routine or usual care (the typical control condition), telehealth interventions yielded significant benefits for persons with dementia (depressive symptoms) as well as for their caregivers (perceived competence). In addition, telehealth interventions show great promise as efficient, cost‐effective, and accessible strategies, which corresponds to past findings that telehealth appears to positively influence not only persons with dementia but also a wide range of other populations (i.e., stroke survivors, victims of heart failure or other cardiovascular diseases, adolescent sexual health, and HIV/AIDS survivors) (Saragih, Imanuel, Osingada, et al, 2021; Saragih, Imanuel, Porta, & Lee, 2021; Saragih, Tarihoran, Batubara, et al, 2021; Valkanova et al, 2017). More importantly, this suggests that including care delivery through telehealth modality may be a viable approach to guarantee continuity of care, address various care needs remotely, and promote favorable patient outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…In comparison with routine or usual care (the typical control condition), telehealth interventions yielded significant benefits for persons with dementia (depressive symptoms) as well as for their caregivers (perceived competence). In addition, telehealth interventions show great promise as efficient, cost‐effective, and accessible strategies, which corresponds to past findings that telehealth appears to positively influence not only persons with dementia but also a wide range of other populations (i.e., stroke survivors, victims of heart failure or other cardiovascular diseases, adolescent sexual health, and HIV/AIDS survivors) (Saragih, Imanuel, Osingada, et al, 2021; Saragih, Imanuel, Porta, & Lee, 2021; Saragih, Tarihoran, Batubara, et al, 2021; Valkanova et al, 2017). More importantly, this suggests that including care delivery through telehealth modality may be a viable approach to guarantee continuity of care, address various care needs remotely, and promote favorable patient outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Within the decade of study, videoconferencing was also the most reliable and proven intervention strategy to improve a stroke survivor's ability to perform ADLs in both the acute and post‐acute settings (Chen et al, 2017; Li et al, 2020; Saywell et al, 2021; Wu et al, 2020). A recent systematic review also reported that videoconferencing interventions significantly improve ‘the performance of ADLs by stroke survivors (Saragih et al, 2021). In line with work by others, these findings suggest that videoconferencing is feasible, acceptable, beneficial, and able to significantly improve the functional performance of stroke survivors (Beit Yosef et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Young stroke survivors endorsed online service delivery as a preferred method to solve the unmet needs of living with stroke (Keating et al, 2021). It has also been suggested that a combination of selfmanagement and telehealth could offer promising interventions (Saragih et al, 2021). Telehealth applications can be particularly helpful for messaging, telephone, video conferencing, and online platforms and these are very applicable for patients at home otherwise limited by time and distance (Anderson et al, 2022;Hwang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%